2017
DOI: 10.1155/2017/4120862
|View full text |Cite
|
Sign up to set email alerts
|

Active Flow Control in a Radial Vaned Diffuser for Surge Margin Improvement: A Multislot Suction Strategy

Abstract: This work is the final step of a research project that aims at evaluating the possibility of delaying the surge of a centrifugal compressor stage using a boundary-layer suction technique. It is based on Reynolds-Averaged Navier-Stokes numerical simulations. Boundary-layer suction is applied within the radial vaned diffuser. Previous work has shown the necessity to take into account the unsteady behavior of the flow when designing the active flow control technique. In this paper, a multislot strategy is designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…In addition, with the effect of the injection, a decrease was observed in the efficiency and pressure ratio. Marsan et al [13] carried out one of the most detailed numerical suction control study in the literature. In their studies, suction actuators were defined on the hub surface of the diffuser blade and the simulations were conducted by defining 1% of the surge flow rate as suction from 3 actuators.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the effect of the injection, a decrease was observed in the efficiency and pressure ratio. Marsan et al [13] carried out one of the most detailed numerical suction control study in the literature. In their studies, suction actuators were defined on the hub surface of the diffuser blade and the simulations were conducted by defining 1% of the surge flow rate as suction from 3 actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence showed that the control method must act upon the flow field within the vaneless space of diffuser to improve stability. Additionally, Marsan 12 proposed a multi‐slot boundary‐layer suction technique on the radial vaned diffuser of a centrifugal compressor, which achieved a remarkable increase in stable operating range by reducing the interaction between the hub‐corner separation vortex and the impeller trailing edge vortex shedding. As noted above, active control methods require additional energy input and need to be equipped with complex configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Onesided diffuser clearance showed no negative impact on the operation or loss behavior of the centrifugal compressor, while improving its pressure ratio and efficiency. Marsan et al 12 processed suction slots at different positions along the radial direction of a diffuser; the boundary-layer suction technique improved compressor stage performance and delayed hubcorner separation.…”
Section: Introductionmentioning
confidence: 99%
“…Marsan et al. 12 processed suction slots at different positions along the radial direction of a diffuser; the boundary-layer suction technique improved compressor stage performance and delayed hub-corner separation.…”
Section: Introductionmentioning
confidence: 99%